Men's Experiences Viewing an HIV/AIDS Prevention Education Film by and for Women - Rosanna F. DeMarco PhD, APRN, BC, ACRN; Chad A. Minnich MAVA (American Journal of Men's Health, 2007)
The purpose of this study is to understand (a) the experience of men viewing the film Women's Voices Women's Lives ( WVWL ), a prevention education film for and by heterosexual African American women living with HIV/AIDS in the United States, and (b) the perceived needs of male viewers on how to best access effective HIV/AIDS prevention messages. A postviewing structured written survey was completed addressing the experience of viewing the film and HIV prevention services in the community, respectively ( N = 16). Responses include stunning realization and anger that motivated viewers to get immediately screened for HIV. In addition, the men felt they were informed about HIV risk through the courage and candidness of the women describing their experience. Participants reported that a film similar to WVWL should be made for heterosexual/bisexual men. The authors conclude film prevention messages are a powerful means to convey health education ideas.